THERMAL MODELLING AND SIMULATION OF SAGS AND SINGLE FLASH POWER PLANT - MECCA SUFYANA (NIM : 22610008); Pembimbing : Dr. Abdurrachim, CANDRA
Thermodynamics evaluation on Steam Above Ground System (SAGS) pipe and geothermal power plant system is required for analysis, measurement, inspection, and testing in order to improve the operational efficiency of the system. The calculation of the evaluation is complex and it takes long time to calculate manually because of the calculation processes and iterations workload. Therefore, this thesis explains about software-based interface that uses Windows features to create model and thermal simulation of heat loss and pressure drop calculations on pipe, and also mass and energy balance in the geothermal power plant system. The methodology for developing the software is Waterfall and designing of software using Unified Modelling Language (UML). This software has been validated using a series of Wayang Windu (WWQ-3) pipes and 14 data fitting pipe to validate SAGS system, Kamojang geothermal power plant unit 2 and 3 to validate power generation that is using gas removal system with two ejectors which are installed in series, and Kamojang geothermal power plant unit 4 to validate power generation that is using hybrid system with combination from ejector and liquid ring vacuum pump. WWQ-3 has well head pressure 12,7 bar-a, enthalpy 2745 kJ/kg, total mass flow 9,6 kg/s results total heat loss 8,14 kW and total pressure loss 0,13 bar-a with Harrison-Freeston method, 0,12 bar-a with Zhao-Freeston method, and 0,19 bar-a with Beggs-Brill method. All those methods get less than 1% error, which Beggs-Brill method give the best estimation. Kamojang geothermal power plant unit 2 and 3 generates power 55.294 MW with 0,53% error, Kamojang geothermal power plant unit 4 generates power 60.218 MW with 0,36% error and so with the others component of power generation get less than 1% error in average. Comparison between model and data comply the expected minimum error, so the model is considered to be valid and can be used for simulation.